Making Transport Work for Women and Men : Challenges and Opportunities in the Middle East and North Africa, Lessons from Case Studies - World Bank (Washington, DC, 2014)
Transport is not 'gender neutral'. Men and women hold different socio-economic roles and responsibilities that are associated with different patterns of transport access, needs, and use. Yet, there is often not much recorded evidence on the differences in gender travel needs between men and women, in urban areas in particular. Transport planning has not routinely addressed these differences and sex-disaggregated data on transport needs and patterns is very limited. The present regional report summarizes the findings and recommendations of four separate case studies on gender and transport conducted in Casablanca, Morocco, Sana'a and rural Yemen, and Nablus, Jenin, and Tulkarem in the northern part of the West Bank, during between September 2008 and September 2009. The main objective with summarizing the case studies into a regional report is to provide a regional overview relevant for a better understanding of how transport infrastructure and services are facilitating or constraining mobility by gender in the MENA region. In particular, the gender differences in access to resources, markets training, information and employment. The report also aims to review other country experience and good practice to help identify priority areas for public intervention to improve women's mobility and enhance their access to economic empowerment relevant for MENA and other regions.